An Appearance Data‐Driven Model Visualizes Cell State and Predicts Mesenchymal Stem Cell Regenerative Capacity (Small Methods 8/2022). Issue 8 (17th August 2022) - Wu, Di; Zhao, Lu; Sui, Bingdong; Tan, Lingping; Lu, Lu; Mao, Xueli; Liao, Guiqing; Shi, Songtao; Cao, Yang; Yang, Xiaobao; Kou, Xiaoxing
Abstract : Inside Front Cover In article number 2200087, Cao, Yang, Kou, and co‐workers constructed an appearance data‐driven mathematical model that excavates four optimal fitted indices, including nucleus roundness, nucleus/cytoplasm ratio, side‐scatter height, and ERK1/2 to evaluate the regenerative capacity of mesenchymal stem cells (MSCs) in vitro. This work provides a potential approach to quantify MSCs' capability in basic and translational studies.